Sex Differences in Academic Rank in US Medical Schools in 2014 - Jena, Anupam B. (JAMA, 2015)
IMPORTANCE: The proportion of women at the rank of full professor in US medical schools has not increased since 1980 and remains below that of men. Whether differences in age, experience, specialty, and research productivity between sexes explain persistent disparities in faculty rank has not been studied. OBJECTIVE: To analyze sex differences in faculty rank among US academic physicians. DESIGN, SETTING, AND PARTICIPANTS: We analyzed sex differences in faculty rank using a cross-sectional comprehensive database of US physicians with medical school faculty appointments in 2014 (91 073 physicians; 9.1% of all US physicians), linked to information on physician sex, age, years since residency, specialty, authored publications, National Institutes of Health (NIH) funding, and clinical trial investigation. We estimated sex differences in full professorship, as well as a combined outcome of associate or full professorship, adjusting for these factors in a multilevel (hierarchical) model. We also analyzed how sex differences varied with specialty and whether differences were more prevalent at schools ranked highly in research. EXPOSURES: Physician sex. MAIN OUTCOMES AND MEASURES: Academic faculty rank. RESULTS: In all, there were 30 464 women who were medical faculty vs 60 609 men. Of those, 3623 women (11.9%) vs 17 354 men (28.6%) had full-professor appointments, for an absolute difference of −16.7%(95% CI, −17.3% to −16.2%). Women faculty were younger and disproportionately represented in internal medicine and pediatrics. The mean total number of publications for women was 11.6 vs 24.8 for men, for a difference of −13.2 (95% CI, −13.6 to −12.7); the mean first- or last-author publications for women was 5.9 vs 13.7 for men, for a difference of −7.8 (95% CI, −8.1 to −7.5). Among 9.1% of medical faculty with an NIH grant, 6.8%(2059 of 30 464) were women and 10.3% (6237 of 60 609) were men, for a difference of −3.5%(95% CI, −3.9% to −3.1%). In all, 6.4% of women vs 8.8% of men had a trial registered on ClinicalTrials.gov, for a difference of −2.4%(95% CI, −2.8% to −2.0%). After multivariable adjustment, women were less likely than men to have achieved full-professor status (absolute adjusted difference in proportion, −3.8%; 95% CI, −4.4% to −3.3%). Sex-differences in full professorship were present across all specialties and did not vary according to whether a physician’s medical school was ranked highly in terms of research funding. CONCLUSIONS AND RELEVANCE: Among physicians with faculty appointments at US medical schools, there were sex differences in academic faculty rank, with women substantially less likely than men to be full professors, after accounting for age, experience, specialty, and measures of research productivity.